ISOLATION OF MICROCRYSTALLINE CELLULOSE FROM MEDANG WOOD (Neolitsea latifolia) - Sunardi Sunardi; Amelia Lestari; Ahmad Budi Junaidi; Wiwin Tyas Istikowati (Konversi, 2019)
Abstract - Research on the effect of the use of HCl concentrations in the hydrolysis process of cellulose from medang wood (Neolitsea latifolia) on the characteristics of microcrystalline cellulose has been studied. The purpose of this study was to determine the effect of HCl concentration on the characteristics of microcrystalline cellulose. The analysis carried out included yield, pH, color, functional group characterization using FTIR and crystallinity index using XRD. The hydrolysis process was carried out at 105 °C for 15 minutes with variations in HCl concentrations of 1.5 N, 2.5 N and 3.5 N. Based on the results of the research conducted, the results showed that the use of variations in the concentration of HCl in the hydrolysis process affected the yield, color, TCI (Total Crystallinity Index) value of FTIR data and crystallinity index of XRD data. The yield of microcrystalline cellulose produced from each variation of concentration was 64.41, 61.94 and 53.99. The color of microcrystalline cellulose is getting darker as the concentration of HCl is used. Based on FTIR data, the TCl value of microcrystalline cellulose from each variation of concentration was 0.861%, 0.907% and 0.976%. XRD data shows an increase in crystallinity index produced from each variation in concentration on microcrystalline cellulose amounted to 80.52%, 82.17% and 83.49%.